SEARLE’S ILLOCUTIONARY SPEECH ACTS THEORY IN BEYOND THE BLACKBOARD MOVIE BY CAMILE THOMASSON - Nuryani Nisa Hayati (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
This research paper explores the illocutionary speech act used by the main character in Beyond the Blackboard movie according to Searle's theory. The study is motivated by the need to understand the context of illocutionary acts and its practical implications for future linguistic research. The researcher employed descriptive qualitative method to analyze main character dialogues with other characters in Beyond the Blackboard movie. The analysis was conducted over one semester, allowing for a comprehensive examination of the types of illocutionary speech uttered by the main character of Beyond the Blackboard movie. The researcher used deductive thematic analysis for analyzing data. The findings revealed all five types of Searle’s illocutionary speech act utilized by the main character in the movie namely directive, representative, commissive, expressive and declarative. The result showed there are 198 utterances containing illocutionary speech act uttered by the main character. From the total of 198, the researcher found 117 utterances containing directive, 48 utterances containing representative, 17 utterances containing commissive, 11 utterances containing expressive, and 5 utterances containing declarative. The dominantly used speech act was directive for the reason that the main character as a teacher needs to guide and direct the students. The study highlights the importance of understanding types of speech and its context in facilitating clear communication. Ultimately, this work aims to inspire further investigations in the field of linguistics and provide valuable insights for educators and researchers alike in speech acts study.